(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
Soil fertility is a vital component of stable society because it ensure growth of plant needed for survival of living organisms. Fertilizers are normally applied to the soil without considering the specific nutrients requirement of the plant, therefore fertilizer use is not rationalized. This study aimed at evaluating the soil fertility for the appropriate recommendation of fertilizer amount and composition for maize production. This will be achieved by assessing the nutrient contents (N, P and K) of the soil and evaluating the nutrient supply using QUEFTSmodel and identify the appropriate fertilizer requirement for recommendation. The sampling area was selected purposively to include area where maize is the major crop grown. Grid soil survey technique was adopted whereby ten soil samples were collected using composite sampling techniques.The results shows that, the mean and standard deviation of the nutrient are N (0.12%±0.03), P (1.36±0.43), K (0.01±0.01) and pH (6.44±0.18). The nutrient supply were recorded as SN= 148.9, SP= 0.09 and SK= 37.45, however it is not all the amount of nutrient in supply form can be absorbed by the plant. The fertility factor rating revealed that N and K ranked high and P ranked low. Based on these analyses, 60kg K2O (nutrient rates/ha) and MOP (100kg/ha) at planting are recommended for maize production in the area.